Reflection seismic study of the Siljan Ring impact structure: Mora - Migrated data - Juhlin, Christopher; Sturkell, Erik; Ebbestad, Jan Ove R.; Lehnert, Oliver; Högström, Anette E. S.; Meinhold, Guido (Uppsala University, 2018)
Two new reflection seismic profiles over the Paleozoic successions of the western part of the Siljan Ring impact structure were acquired during 2011, the Mora and the Orsa profile. This data set concerns the Mora profile. The profile has length of c. 10 km and the processed data image the geological section to about 3 km depth. During the survey, 391 source points (VIBSIST 3000) were recorded by 320 receiver channels for 30 seconds. From this recording, the following data sets were generated and are published here: 1) decoded and quality controlled raw data; 2) pre-processed (shot geometry applied) data; 3) stacked data; 4) migrated data; 5) depth converted data and velocity field.
Key acquisition parameters are:
Number of channels: 320 (160-160)
Near offset: 0m
Geophone spacing: 10 m
Geophone type: 28 Hz single
Source spacing: 20 m
Source type: VIBSIST 3000
Hit interval between hammer blows: 100-200 ms
Sweeps per source point: 3-4
Nominal fold: 80
Recording instrument: SERCEL 428UL
Sample rate: 1 ms
Field low cut: Out
Field high cut: 400 Hz
Record length: 30 s
Profile length: 10 km
Source points: 391
Dates acquired: 3/6-9/6: 2011

This dataset contains processed data of the Mora profile:
Processing steps for this data set:
1: Read decoded VIBSIST data
2: Bulk static shift to zero time
3: Apply geometry
4: Pick first breaks
5: Spherical divergence correction
6: Trace editing
7: Trace balance: 0–3000 ms
8: Spectral equalization: 0–600 ms: 50–80–200–240 Hz; 700–1500 ms: 40–70–180–240 Hz
9: Time variant bandpass filter: 0–400 ms: 50–80–240–360 Hz; 450–600 ms: 45–70–210–300 Hz; 700–1000 ms: 40–60–180–270 Hz; 1100–3000 ms: 35–50–150–225 Hz
10: Refraction statics: datum 160 m, replacement velocity 3000 m/s
11: Residual statics
12: Median filter: 11 traces, 3 samples, 5300 m/s, subtract
13: AGC: 50 ms
14: Mute: top and bottom
15: Residual statics
16: Velocity analysis
17: NMO correction: 70% stretch mute
18: Trace balance
19: FX Decon: 19 trace window
20: No dip filter
21: Trace balance
22: Stolt migration: 200–3000, 1000–4000 ms/s

Processed seismic data stored as one file for the enitre seismic profile, according to SEG technical standard SEG-Y revision 1 (SEG-Y_r1.0, 2002); https://seg.org/Publications/SEG-Technical-Standards

År 2011 gjordes två nya reflexionsseismiska undersökningar över västra delen av Siljansringen, Mora och Orsa profilerna. Siljansringen är en struktur som uppkom för ca 377 miljoner sedan genom ett meteoritnedslag. Mora profilen (detta dataset) är ca 10 km lång och visar de geologiska strukturerna till ca 3 km djup. Den seismiska bilden visar att den geologiska följden i de siluriska och ordoviciska sedimentera bergarterna är starkt störd.

En mer detaljerad beskrivning av datasetet som inkluderar alla viktiga parametrar är tillgängligt på den engelska katalogsidan: https://snd.gu.se/en/catalogue/study/SND1050

Bearbetade data för Mora-profilen.
Mer information på den engelska katalogsidan: https://snd.gu.se/en/catalogue/study/SND1050.
Reflection seismic study of the Siljan Ring impact structure: Mora - Migrated data
Keywords: EARTH SCIENCE; geological disaster; geologisk katastrof; geophysics; geofysik; research; forskning; Geophysics; Geofysik; Geoscientific Information; Geovetenskap